2008
DOI: 10.1021/ic801459s
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Valence Octanuclear Iron−Oxo Pyrazolate: Assessment of Electronic Delocalization by Structural and Spectroscopic Analysis

Abstract: A formally FeIII7FeII complex, containing an inner Fe4O4-cubane and four peripheral Fe-centers, is derived from the one-electron reduction of its FeIII8 precursor. Spectroscopic analysis of the former reveals that the redox activity of this Fe8-system is confined within its cubane core. The resulting (Fe4O4)3+-cubane, which is valence-delocalized in the NMR, Mössbauer and IR, but valence-trapped in the X-ray photoelectron spectroscopy (XPS) timescale, is better described as a Robin-Day class-II system by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 19 publications
(37 reference statements)
4
50
1
Order By: Relevance
“…[2021] We have previously reported the reduction of organosoluble [Fe 8 ] 0 to [Fe 8 ] − species by electrochemical and chemical means – stoichiometric addition of [BH 4 ] − . [10, 11] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2021] We have previously reported the reduction of organosoluble [Fe 8 ] 0 to [Fe 8 ] − species by electrochemical and chemical means – stoichiometric addition of [BH 4 ] − . [10, 11] …”
Section: Resultsmentioning
confidence: 99%
“…In one case, the first reduction product, [Fe 8 (μ 4 -O) 4 (μ-4-Cl-pz) 12 Cl 4 ] − , has been isolated and fully characterized: It is readily recognized by its near-IR intravalence charge transfer (IVCT) band and shift of the ν (Fe-O) stretch in the IR, but is structurally indistinguishable, within experimental error, from its all-Fe III parent compound. [11] Visual inspection of a three-dimensional model of the [Fe 8 (μ 4 -O) 4 (μ-pz) 12 Cl 4 ] complex, or the space-filling diagram (Figure 1c), shows that its approximately spherical surface is defined by H- and Cl-atoms, rendering it highly hydrophobic. Consequently, [Fe 8 (μ 4 -O) 4 (μ-4-R-pz) 12 X 4 ] complexes with R=H, Cl, Br and CH 3 are all soluble in common organic solvents (methylene chloride, chloroform, tetrahydrofuran, acetone, toluene, acetonitrile, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[1] In recognition of this, many groups have been using chelating ligands containing carboxylate functions and other functionalities in order to determine which parameters are important in controlling the speciation of iron. These studies have led to a wide variety of polyiron clusters containing bridging oxygen atoms and Fe 4 , Fe 6 , Fe 8 , Fe 10 , Fe 11 , Fe 12 , and Fe 16 centers. [2][3][4][5][6][7][8][9] It has been demonstrated that the hydrolysis of iron salts can be controlled by organic ligands so as to yield soluble molecular aggregates with nanometer dimensions, which can often be isolated in crystalline form and structurally characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Though some work has been carried out directly in aqueous environments, the use of non-aqueous media with a low water content has led to the synthesis of an unexpected variety of polynuclear clusters. [2][3][4][5][6][7][8][9] Of particular relevance to the present study is a family of octanuclear [Fe 8 (μ 4 -O) 4 (μ-4-R-pz) 12 X 4 ] (Fe 8 ) clusters (R = CH 3 , H, and Cl; X = Cl, Br; pz = pyrazolate), which were generated in one-pot reactions of FeX 3 , 4-R-pz, and base in air. [10][11][12][13][14] Notably, spectroscopic and electrochemical properties relative to those of the previously reported Fe 8 clusters based on pyrazolate ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation